Metahouse: Noise‐Insulating Chamber Based on Periodic Structures. Issue 1 (9th November 2022) - Krasikova, Mariia; Krasikov, Sergey; Melnikov, Anton; Baloshin, Yuri; Marburg, Steffen; Powell, David A.; Bogdanov, Andrey
Abstract: Noise pollution remains a challenging problem requiring the development of novel systems for noise insulation. Extensive work in the field of acoustic metamaterials has led to various ventilated structures which, however, are usually demonstrated for rather narrow regions of the audible spectrum. In this work, the idea of metamaterial‐based systems is further extended, developing the concept of a metahouse chamber representing a ventilated structure for multiple band noise insulation. Broad stop‐bands originate from strong coupling between pairs of Helmholtz resonators constituting the structure. The averaged transmission −18.6 dB are demonstrated numerically and experimentally within the spectral range from 1500 to 16 500 Hz. The sparseness of the structure together with the possibility to use optically transparent materials suggest that the chamber may be also characterized by partial optical transparency depending on the mutual position of structural elements. The obtained results are promising for development of novel noise‐insulating structures advancing urban science. Abstract : Metamaterial‐based ventilated chamber for broadband noise insulation with averaged transmission −18.6 dB within the spectral range from 1500 to 16 500 Hz. The chamber is designed to be simple for manufacturing and assembling. At the same time, the requirements for materials are easily met and the structure can be made of ecologically friendly and optically transparent materials.